Design of a Novel Hybrid Concentrated Photovoltaic–Thermal System Equipped with Energy Storages, Optimized for Use in Residential Contexts - Carmine Cancro; Valeria Palladino; Aniello Borriello; Antonio Romano; Luigi Mongibello (Solar)
Concentrated photovoltaic (CPV) technology is based on the principle of concentrating direct sunlight onto small but very efficient photovoltaic (PV) cells. This approach allows the realization of PV modules with conversion efficiencies exceeding 30%, which is significantly higher than that of the flat panels. However, to achieve optimal performance, these modules must always be perpendicular to solar radiation; hence, they are mounted on high-precision solar trackers. This requirement has led to the predominant use of CPV technology in the construction of solar power plants in open and large fields for utility scale applications. In this paper, the authors present a novel approach allowing the use of this technology for residential installations, mounting the system both on flat and sloped roofs. Therefore, the main components of cell and primary lens have been chosen to contain the dimensions and, in particular, the thickness of the module. This paper describes the main design steps: thermal analysis allowed the housing construction material to be defined to contain cell working temperature, while with deep optical studies, experimentally validated main geometrical and functional characteristics of the CPV have been identified. The design of a whole CPV system includes thermal storage for domestic hot water and a 1 kWh electrical battery. The main design results indicate an estimated electrical conversion efficiency of 30%, based on a cell efficiency of approximately 42% under operational conditions and a measured optical efficiency of 74%. The CPV system has a nominal electric output of 550 Wp and can simultaneously generate 630 W of thermal power, resulting in an overall system efficiency of 65.5%. The system also boasts high optical acceptance angles (±0.6°) and broad assembly tolerances (±1 mm). Cost analysis reveals higher unit costs compared to conventional PV and CPV systems, but these become competitive when considering the benefit of excess thermal energy recovery and use by the end user.